Living Hadith: The Challenge of Tawhid and the Practice of Tamimah Among Pregnant Women in Bagan Dalam Village, Batubara - Arifah Zahirina; Agusman Damanik (Lembaga penelitian dan pengabdian kepada masyrakat, 2026)
The practice of using amulets among pregnant women continues in Bagan Dalam Village, Batubara Regency, as a means to protect the pregnancy from supernatural disturbances. Objective: This study aims to describe the types of amulets used and analyze the practice from a Hadith perspective. Additionally, it serves as an academic reference to distinguish between permissible and prohibited practices under Islamic law (Sharia), particularly regarding protective measures for pregnant women. Methods: A qualitative approach with a case study design was employed. Data were collected through observation, in-depth interviews with five pregnant women who use amulets, and field documentation. A descriptive analysis was conducted by referring to the Hadiths of Prophet Muhammad ﷺ concerning tamimah (amulets). Results: The findings indicate that the amulets consist of natural elements, including net fibers, turmeric bangles, sappan wood (secang wood), tridatu threads, porcupine quills, gambier, nutmeg, coriander, cloves, and woven bags. These items were obtained based on family recommendations and were blessed by a shaman or traditional healer (smart person) before use. This practice is driven by fear of supernatural disturbances and the strong influence of family tradition. Conclusion: Based on the Hadith analysis, the use of these amulets contradicts the teachings of the Prophet ﷺ, who strictly prohibited tamimah and consulting shamans. Therefore, reinforcing the understanding of Tawhid (the oneness of God) through religious education is of paramount importance, alongside encouraging the implementation of ruqyah syar'iyyah (Sharia-compliant protective prayers) as a religiously legitimate means of protection.